2014
DOI: 10.1177/0972150914535067
|View full text |Cite
|
Sign up to set email alerts
|

Liberalization and Structural Change in Australian Automotive Industry: An Analysis of Trade and Productivity Performance: 1962–2008

Abstract: This article investigates the effects of policy liberalization on structural change in the Australian automotive industry, with a focus on trade and productivity performance. While there has been a rise in exports and imports, productivity fell significantly following policy liberalization. The absolute fall in productivity appears to have been linked with the excess production capacity and higher production costs. The post-liberalization fall in productivity may signal the beginning of a turnaround, but only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…During the entire study period, TFP grew at about 1.5% on average per annum -much lower than growth in factor inputs and value added (Table 1). When productivity growth is separated into the pre-and post-reform period performance, the average annual growth in TFP dropped from over 4% per annum in the pre-reform period to −0.91% in the post-reform period (Bopage and Sharma 2014b). This absolute fall in productivity appears to have been linked with poor capacity utilization brought about by intense competition in both domestic and export markets, leading to a fall in output (see Appendix 1, column two).…”
Section: Productivity Performance Of the Australian Passenger Motor Vmentioning
confidence: 93%
“…During the entire study period, TFP grew at about 1.5% on average per annum -much lower than growth in factor inputs and value added (Table 1). When productivity growth is separated into the pre-and post-reform period performance, the average annual growth in TFP dropped from over 4% per annum in the pre-reform period to −0.91% in the post-reform period (Bopage and Sharma 2014b). This absolute fall in productivity appears to have been linked with poor capacity utilization brought about by intense competition in both domestic and export markets, leading to a fall in output (see Appendix 1, column two).…”
Section: Productivity Performance Of the Australian Passenger Motor Vmentioning
confidence: 93%
“…Lionel Bopage and Kishor Sharma (2014) have focused on trade and productivity performance. It has been found that there has been a rise in exports and imports but productivity fell significantly following policy liberalization.…”
Section: Literature Reviewmentioning
confidence: 99%